The teaching of science and technology in an interdisciplinary context: Approaches for the primary school - Macleod, Sinclair; Mills, George (UNESCO)
This document purposed to test interdisciplinary approaches in several countries and to disseminate the results of this testing to other interested Member States. Two of these approaches based on experience gained in the Primary Science Development Project in Scotland, are described and exemplified in this document. The main aim in presenting these approaches is to show how specific aspects of science and technology can be developed within a study which involves a variety of curricular areas such as art, music, mathematics and language.
Note: Date of issue not indicated in document
Keywords: science and technology; primary school